Pharmacognostical and Proximal Analysis of Two different Extracts (Methanol and Aqueous) of Indian Endangered Coscinium fenestratum Stem - Das, Kuntal (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: Coscinium fenestratum (CF) (Family: Menispermaceae), an endangered and highly commercial medicinal plant of traditional system of medicine. Stem is commercially important which have multiple medicinal used and therapeutic efficacy. The objective of the study is to evaluate the effect of extraction, content of elements and their correlation on proximate analysis and detection of compound in various extracts of Indian endangered Coscinium fenestratum stem. Materials and Methods: Proximate analysis in terms of moisture content, ash values, extractive values and crude fibres are determined as per AOAC method. Arrangement of stem fibres is detected with SEM. Presence of secondary metabolites in both the extracts performed through chemical tests. Elemental analysis was carried out by digestion method using Atomic Absorption Spectrophotometer. Results: Powder microscopy as well as SEM analysis revealed the presence of fibres, cork cells, cortex, tracheids, pitted wood elements and Xylems, Prismatic calcium oxalate crystals, stone cells, Medullary rays, phloem fibres etc. Elemental analysis revealed high content of elements in microwave extracted aqueous extract than soxhlet extracted sample. Chemical tests resulted high content of alkaloid, phenolics and flavonoids in microwave extracted methanolic extract. Conclusion: This was the first report on this plant about basic mechanism for presence of phytoconstituents in higher amount influenced by various elements as well as anatomical identification of stem cells and tissues through SEM analysis.
Keywords: Coscinium fenestratum; Proximate; Elemental analysis; Microscopic; character; SEM